Internal auditing in the face of banking fraud, application of the Benford law on Algerian private bank - Mehdi Bouchetara; Abdelkader Nassour (UTMS Journal of Economics, 2020)
In this paper, we analyze the importance of internal audit against banking fraud in order to ensure banking stability, using mathematic approach. We explain the steps involved in setting up an anti-fraud plan. Then, we implement two phases of this plan, namely the evaluation of the degree of exposure to the risk of fraud in a large private bank in Algeria, and then we propose a tool for detecting fraudulent acts, the Benford law. The result confirms that internal audit is an indispensable function. It enables the bank to have a solid assurance that the risks, to which it is exposed, including the risk of fraud, are under control.
Keywords: M42; M49; 330; Internal audit; banking fraud; benford law; Algerian bank